Osteoporosis Self Assessment Tool for Asian (OSTA) Index in Comparison to Quantitative Ultrasound of the Calcaneal in Predicting Low Bone Density. - Sherchan, Binod; Lamichhane, Arjun; Mahara, Deepak Prakash (Nepal Orthopaedic Association Journal, 2014)
Introduction: Osteoporosis represent a worldwide public health problem, frequently resulting in fractures and leading to psychological problem, social consequences, functional limitation and poor quality of life. So it is important to identify those people who have high risk of osteoporosis, in order to reduce the incidence of osteoporotic fractures. The Osteoporosis Self-Assessment Tool for Asians (OSTA) index is a simple tool based on age and body weight. Calcaneal quantitative ultrasound (QUS) is another simple and low-cost instrument used to prescreen osteoporotic subjects. The aim of this study was to correlate between these two screening methods and to validate usefulness of Osteoporosis self assessment tool for Asian ( OSTA) in comparison with QUS of the calcaneum for the prediction of low bone density in Nepalese women. Methods: This was a two-year descriptive observational study comprising 100 subjects performed at TU Teaching Hospital, Kathmandu, Nepal, from 2007 January to 2009 January who completed semi structured questionnaire with subsequent measurement of Quantitative Ultrasound (QUS) of the calcaneum. The sensitivity, specificity, and diagnostic accuracy of OSTA index was validated with the QUS T-score. Results: When the risk category was defined as OSTA index ≤ -1, and low QUS value as t-score ≤ -2.5, the sensitivity, specificity and diagnostic accuracy of the index were 93.3%, 56.5%, and 62% respectively, and the area under the curve was 0.7651. When the low QUS value was taken as t score ≤ -1.0, the sensitivity, speciÞ city and diagnostic accuracy was 85.2%, 89.1% and 87% respectively. Conclusions: The OSTA index, a simple and free risk assessment tool, can be used to estimate the prevalence of low QUS values in Nepalese women and may help to increase awareness and prevention of low bone mineral density. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9524 NOAJ July-December 2013, Vol 3, Issue 2, 20-25